Selection of suitable filter materials for subsurface flow constructed wetland systems for wastewater treatment in rice noodle handicraft village - Anh, Bui Thi Kim; Thanh, Nguyen Van; Phuong, Nguyen Minh; Ha, Nguyen Thi Hoang; Duong, Nguyen Trieu; Kim, Dang Dinh; Yen, Nguyen Hong; Chuyen, Nguyen Hong (Vietnam Journal of Science and Technology, 2024)
This study aims to select suitable filter materials for Subsurface Flow Constructed Wetlands (SSF CW) to treat wastewater from rice noodle handicraft villages, based on a combination of new materials (plastic waste and rice husk) and traditional substrates (limestone, gravel, and sand). Four SSF CW models using different filter materials were tested during three months, including CW1 (limestone, gravel, and sand), CW2 (sand, plastic waste, and gravel), CW3 (sand + rice husk, limestone, and gravel), and CW4 (sand + rice husk, plastic waste, and gravel). The results indicated that CW3 and CW4 systems were more effective to plant growth. Replacing limestone with plastic waste did not show a significant difference in treatment efficiency (p > 0.05), however the addition of rice husk decreased the efficiency of organic matter treatment while increasing nutrient treatment efficiency (p < 0.05). The highest treatment efficiencies for TSS and COD were observed in CW1, at 83.89 ± 1.38 % and 79.56 ± 1.36 %, respectively. Meanwhile, the highest treatment efficiencies for TN, NH4+, and TP were recorded in CW4, at 80.14 ± 2.76 %, 88.39 ± 1.62 %, and 82.22 ± 2.51 %, respectively. The effluent water from all four SSF CW models met the Vietnamese standard for wastewater quality (QCVN 40:2011/BTNMT, column B). This study demonstrates the potential of using a combination of plastic waste, rice husk, and sand as suitable filter substrates for SSF CW in treating wastewater from rice noodle handicraft villages.